From Sustainability Practice, Lovemark, Engagement, to Fast Fashion Loyalty Stage: Gender as Moderation - Pranoto, Danu Eko; Hussein, Ananda Sabil; Suryadi, Nanang; Wu, Hung-Che (Universitas Brawijaya, Indonesia, 2025)
Changes in consumer behavior that prioritize the sustainability agenda have challenged the fast fashion sector to grow without becoming enemies of the environment while maintaining their loyal customers. Therefore, this study aims to increase fast fashion brand loyalty through perceived sustainable marketing, with the mediation of brand love, brand respect, brand engagement in self-concept, and gender moderation. Data were collected through a survey method using questionnaires, and 260 respondents were obtained. The data were analyzed using SEM-PLS. The results demonstrate that perceived sustainable marketing is a precursor to love, respect, engagement, and loyalty. Brand loyalty is influenced by brand respect and engagement, but not by brand love. Moreover, brand engagement is influenced by brand love and respect. Theoretically, this study describes a brand-customer relationship model, from perceived sustainability to the loyalty stage. Unfortunately, gender cannot moderate that relationship. However, practically, this study shows that fast fashion marketers should consider women more likely to consider sustainability campaigns important in influencing the loyalty they give to brands, compared to men.